PERAN BANTUAN SOSIAL DIMASA PANDEMI COVID-19 TERHADAP PEKERJA RENTAN DI KABUPATEN PIDIE - Andi Maulana; Cut Zakia Rizki; Putri Bintusi Syathi; Fitriyani Fitriyani (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractThis study aims to determine the role of social assistance during the Covid-19 pandemic for vulnerable workers in Pidie Regency. The variables in this study include social assistance for vulnerable workers. In this study, the author uses a quantitative descriptive approach. The results of the study indicate that the percentage of vulnerable workers in Pidie Regency who received assistance was more than those who did not receive assistance with a percentage of 68 percent, and all of them came from the government. During the pandemic 78 percent of vulnerable workers in Pidie district relied on savings and loans if there was no assistance at all. Even though they are still working, these vulnerable workers experience a drastic decrease in their income and some are even without income. Furthermore, for vulnerable workers to stay away from risk factors related to the Covid-19 virus, obey the health protocols from the government, in order to stop the wave of the spread of the Covid-19 virus.Keywords: Social Assistance, Vulnerable Workers,Covid-19 Pandemic